Physico-Chemical Studies on Maroon Coloured Karonda (Carissa carandus) Collected from Uttar Pradesh, India - Meena, Vijay Singh; Pratap, Bhanu; Bhatt, K. C.; Pradeep, K.; Meena, N. L.; Kumar, Ashok; Singh, Kuldeep (International Journal of Economic Plants, 2020)
An exploration was conducted to collect genetic variability of Karonda (Carissa carandus), in different district of Uttar Pradesh during 2019-20. Augmenting germplasm is the first and the foremost activity indeed required for this fruit crop improvement as vast diversity still present in different ecosystem. Being a rich source of iron and minerals, it has potential to improve socio economic status and nutrition standard of Indian rural population. All genotype from IC632668 to 0632678 collected from different places of Uttar Pradesh found erect in nature with fruit diameter of 11 to 19 mm and with three distinct colours (white, green and red). Higher variation was reported in fruit weight, leave size, fruit colour, TSS, acidity and vitamin C content. Significant difference among TSS and vitamin C content was recorded. Attractive colour with good fruit size was observed in Accession no. IC-0632675 collected from Chiraigaon district Varanasi with excellent blend of TSS (9.5°B), acidity (1.10) and vitamin C (28 mg 100 g-1).